KOMIK SEBAGAI SARANA KOMUNIKASI PROMOSI DALAM MEDIA SOSIAL - Gede Lingga Ananta Kusuma Putra; Gede Pasek Putra Adnyana Yasa (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Desain dan Bisnis Bali, 2019)
Comics are one of the most effective promotional media because they have pictures, text and storylines. The present development of comics is not only made through conventional processes but can also be done in digital processes. This comic gain is taken to carry out the promotion process. The development of the internet today is very rapid. With the help of internet use it can allow an individual to interact with other individuals without any distance limitations. Social media is one of the developments in digital technology that makes it easy for someone to communicate with people without the distance of their location. Social media is an effective publication tool in the publication of comics that contain promotional content so that messages can be received by the wider community. Comics have various types according to their needs, and one of them is the Comic Strip. In the Comic Strip is an effective choice in carrying out a promotional activity. Stripm comics are a type of comic that only consists of a few panel images. However, when viewed in terms of its contents, this comic has revealed the idea of ​​complete content. With the advantages of Comics and social media, comic publications on social media are one of the effective choices in making a promotion.